Microstructural stability of ODS Fe–14Cr (–2W–0.3Ti) steels after simultaneous triple irradiation. (December 2016) - Šćepanović, M.; de Castro, V.; Leguey, T.; Auger, M.A.; Lozano-Perez, S.; Pareja, R.
Highlights: Two Fe14Cr ODS steels have been simultaneously triple ion-beam irradiated. Their microstructural stability has been analyzed using TEM techniques. Nanoparticles maintain composition and morphology while sizes increase slightly. Abstract: Simultaneous triple-ion beam irradiation experiments with Fe 5+, He + and H + ions were performed to simulate fusion damage on two nanostructured ferritic alloys with nominal composition Fe–14Cr–0.3Y2 O3 and Fe–14Cr–2W–0.3Ti–0.3Y2 O3 . Samples were irradiated at 600 °C to an estimated dose of ∼ 30 dpa, 600 appm He, 1500 appm H, and the effects on the microstructure of these alloys investigated by analytical transmission electron microscopy. The results reveal the development of nanovoids, or small bubbles, undetected in the unirradiated samples, and a virtual compositional stability of the dispersion. Nevertheless, upon irradiation the measured size distribution indicates a slight growth of those dispersoids having the smaller sizes.